Effect of ta’awun on management stickiness of administrative zakat institutions - Mhd. Sarif, Suhaimi; Yahya, Rohaziah (Zes Rokman Resources, 2020)
Zakat institutions are special administrative entities strictly under state law regulations. The basic formation entity embedded management stickiness. Economic phenomenon of stickiness hampered efficiency and productivity of organizations. Management orientation, key stakeholders political actions, and inflexible organisational design contribute to severe management stickiness. This is added with political organizational actions create stickiness phenomenon. Ta’awun enhances teamwork spirituality and religiosity to address management stickiness. This study postulates that the influence of ta’awun reduces stickiness in managing zakat institutions with efficiency and productivity. This study obtains the opinions of residential association leaders through personal interview on the influence of ta’awun in addressing stickiness in zakat institutions. The results of the study suggest that there has been adhoc ta’awun between the community and zakat institutions on seasonal and activism basis.